Prey Luring Coloration of A Nocturnal Semi‐Aquatic Predator. (14th June 2016) - Tso, I‐Min; Zhang, Shichang; Tan, Wei‐Li; Peng, Po; Blamires, Sean J.
Abstract: Body coloration serves a variety of purposes in animals. Diurnal and nocturnal predators such as spiders may use their body coloration to lure prey. We predicted here that the white patches on the forelegs on females of the nocturnal semi‐aquatic spider Dolomedes raptor lure prey, explaining why they are primarily displayed when the spider forages along the water edge. To test our prediction, we developed a color vision model assessing whether the patches are visible to pygmy grasshoppers, the spider's primary prey. We conducted a field experiment using cardboard dummies that resemble D. raptor in size, shape, and color, but with half of them lacking leg patches, and we staged interactions between pygmy grasshoppers and D. raptor with and without leg patches in a greenhouse. We found the white patches to be visible to grasshoppers. The dummies with white patches attracted more grasshopper prey than the dummies without the patches. Moreover, grasshoppers were more attracted to spiders when their white patches were present. Our results supported the hypothesis that the white patches of D. raptor lure prey. Our findings, nevertheless, could not be explained as the spider's body coloration acting as a sensory trap but it should not be ruled out. More studies on a wider range of predators and prey will give more meaningful insights into the co‐evolution of predatory lures and prey sensory modalities.